The -inconsistent- employment precariousness of care work. The necessary legal revaluation - Quintero Lima, María Gema (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2022)
Especially after the COVID19 health crisis, and then the economic and social crisis, it has manifested itself as an inescapable reality, job insecurity in the field of care work. It has to be considered unnecessary, attending to the centrality that care systems would have in the new social constructions of equality. Legal labor regulations, of legal origin, but also conventional, are the cause and effect of an undervaluation of this type of work, eminently carried out by women, with direct positive effects on the employability of other women.
Keywords: care; domestic service; women's work; equality and non-discrimination; decent work